2018
DOI: 10.2174/1874285801812010333
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Tuberculosis and Associated Factors Among Diabetic Patients Attending Hawassa Adare Hospital, Southern Ethiopia

Abstract: Background:Developing countries have a high burden of Tuberculosis (TB); although it is considered as a disease of the past in most developed countries. The end TB strategy was predicted to stabilize or drop the incidence of TB. However, the rising of the prevalence of immune-related diseases like Diabetes Mellitus (DM) are challenging the TB control strategy in high TB burden region. The objective of this study was to determine the prevalence and associated factors of pulmonary tuberculosis in DM patients att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The study revealed that the prevalence of TB and DM comorbidity was 27.3%. This result was higher than studies conducted in South Africa (3.0% [28], Debre Tabor General Hospital (2.71% [29], Hawassa (5.3% [30], Addis Ababa (7.1% [26], and Dessie (6.2% [31]). The higher PTB and DM comorbidity in the study area may be due to lower regular monitoring of DM, a TB prevention programme, the immunity status of the patients, and financial constraints.…”
Section: Discussionmentioning
confidence: 56%
“…The study revealed that the prevalence of TB and DM comorbidity was 27.3%. This result was higher than studies conducted in South Africa (3.0% [28], Debre Tabor General Hospital (2.71% [29], Hawassa (5.3% [30], Addis Ababa (7.1% [26], and Dessie (6.2% [31]). The higher PTB and DM comorbidity in the study area may be due to lower regular monitoring of DM, a TB prevention programme, the immunity status of the patients, and financial constraints.…”
Section: Discussionmentioning
confidence: 56%
“…This finding is higher than previous studies done 5.3% in Ethiopia from Hawassa by Abera et al, 2018. 34 This could be because our study site is a referral site for Tuberculosis-related cases highly TB suspected individuals might include in our study. However, this finding is lower than 15.11% studies in Government hospitals in Addis Ababa by Gebrecherkos et al, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study concluded a common knowledge that the longer duration of DM tends to get TB than the shorter 27 . The immunity of the DM patient is more compromised, particularly for long duration DM as a result of micro-and macro-vascular complications as well as the treatment tolerance of the disease 28 . Indeed much is known about the duration of the DM implying the complication and severity of the diseases as well as the terminal outcome, either in the general complication or especially in the TB occurrence [29][30][31] .The present study did not provide evidence of a longer duration of DM as a risk factor for pulmonary TB, because of the interaction of household contact (OR=63.3) as the most influential factor.…”
Section: Discussionmentioning
confidence: 99%